2021
DOI: 10.1029/2020wr028760
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Distribution Characteristics of Total Dissolved Gas Supersaturation at Confluences

Abstract: Total dissolved gas supersaturation (TDGS) produced by flood flows over a high dam has negative consequences on downstream fish. Reducing the total dissolved gas (TDG) levels and/or providing adequate low‐TDGS fish shelter areas remains a challenge. The presence of a low‐TDG‐saturation (LTS) zone at river confluences can protect the fish from harmful high TDG levels, but the effects of confluence hydrodynamics on the TDGS distribution are not well understood. In this study, three‐dimensional (3D) hydrodynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 77 publications
(153 reference statements)
0
5
0
Order By: Relevance
“…In this study, ANSYS FLUENT 2021R2 was used to solve governing equations using the finite volume method. The RNG k‐ε turbulence model was selected for this study because of the strong turbulence and curved flow lines of the confluent flow (Shen et al., 2021). A mixed unstructured quadrilateral and a triangular grid was used to mesh the study area.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, ANSYS FLUENT 2021R2 was used to solve governing equations using the finite volume method. The RNG k‐ε turbulence model was selected for this study because of the strong turbulence and curved flow lines of the confluent flow (Shen et al., 2021). A mixed unstructured quadrilateral and a triangular grid was used to mesh the study area.…”
Section: Methodsmentioning
confidence: 99%
“…When flow velocity and water depth were thoroughly analyzed, it was determined that the confluence location was suitable for shielding fish from TDG supersaturation. Based on this, Shen et al (2021) used the 3D simulation method to investigate the mechanism influencing the flow ratio and confluence angle on the distribution of TDG concentrations downstream of the confluence. It was discovered that the secondary flow's advection circulation caused higher concentrations of TDG to renew their surfaces more quickly, hastening the release of supersaturated TDG.…”
Section: Abatement Measures In the Release Stagementioning
confidence: 99%
“…Using a three‐dimensional hydrodynamic simulation method, Shen et al. (2021) investigated the impact of flow ratio and confluence angle on TDG release downstream of the confluence. The findings demonstrated that the main influences on the concentration distribution of TDG were inflow TDG, secondary flow, and turbulence intensity.…”
Section: Factors Influencing Tdg Supersaturationmentioning
confidence: 99%
“…TDG super-saturation induces gas bubble disease in fish, thereby adversely impacting the local riverine eco-environment (Wang et al, 2020;Shen et al, 2021). Fish exposure to TDG supersaturated water can cause foam trauma and death-related injuries (Weitkamp and Katz, 1980).…”
Section: Introductionmentioning
confidence: 99%